Mind the (nutrient supply) gap: An assessment of demand and supply limitations for Nitrogen, Phosphorus and Potassium for major crops in Nepal - Chakraborty, Debashis; Sherpa, Sonam Rinchen; Koirala, Pankaj; Baral, Bandhu Raj; Karki, Saral; Sapkota, Shishir; Gathala, Mahesh Kumar; Krupnik, Timothy Joseph (CSISA, 2024)
This work is supported by the USAID/Nepal-funded Cereal Systems Initiative for South Asia (CSISA) 'Building food system resilience to global supply chain and climate shocks in Nepal' Activity supported by USAID/Nepal. CSISA aims to enhance the adoption of resource-conserving and climate-resilient technologies while improving farmers' access to market information and enterprise development, particularly for women farmers through modern innovations and entrepreneurial skills. Working in synergy with regional and national efforts, CSISA collaborates with various public, civil society, and private-sector partners to promote widespread adoption of practices that increase yields with reduced water, labor, and input costs. The initiative supports the integration of innovations into government programs, generates and disseminates knowledge on climate-resilient cropping systems, improves the policy environment for sustainable intensification technologies, and builds strategic partnerships to sustain the benefits of increased cereal system productivity. The project is led by CIMMYT and implemented jointly with IFPRI, IRRI, and IWMI, with support from the Institute for Integrated Development Studies (IIDS) and International Development Enterprises (iDE).